Medication-associated gastrointestinal tract injury - Vieth, Michael; Montgomery, Elizabeth (Virchows Archiv, 2017)
Medication-associated gastrointestinal (GI) tract injury has been known for centuries for some medications. The more recently introduced biologicals are a class of drugs that constantly increases, and as such, the spectrum of GI tract side effects is steadily growing. This review covers not only long-known GI tract side effects of drugs but also those more recently described. A comprehensive but concise list of medications used in daily practice and associated with GI tract injury is presented.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Biologicals; Gastrointestinal (GI); Generic and trade names; Injury; Medication